THE EFFECT OF LEARNING FACILITIES AND PEER ENVIRONMENT ON STUDENT LEARNING ACHIEVEMENT IN ECONOMICS SUBJECT THROUGH LEARNING MOTIVATION - 'Aisy, Fadhlika Nur Rohadatul; Saptono, Ari; Wibowo, Agus (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aimed to determine the direct and indirect effects of learning facilities and peer environment on student achievement in economics subject through learning motivation. This study is a quantitative study with path analysis technique using survey methods with data collection techniques are document student learning outcomes and questionnaires about learning facilities, peer environment, and learning motivation. The population in this study were students of SMA Negeri in Bekasi City with a sample of 190 respondents. The results of the analysis show that (1) learning facilities have a positive and significant direct effect on student learning achievement. (2) the peer environment has a positive and significant direct effect on student achievement. (3) learning motivation has a positive and significant direct effect on student achievement. (4) learning facilities have a positive and significant direct effect on learning motivation. (5) the peer environment has a positive and significant direct effect on learning motivation. (6) learning facilities have a positive and significant indirect effect on student achievement through learning motivation. (7) peer environment has a positive and significant indirect effect on student achievement through learning motivation.